2021
DOI: 10.1111/imj.14843
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy for emergent large vessel occlusion: an Australian primary stroke centre workflow analysis

Abstract: Background Time to successful reperfusion is a critical prognostic factor for acute ischaemic stroke. Mechanical thrombectomy has become the gold standard treatment for emergent large vessel occlusion stroke. The timely delivery of this highly specialised procedure to patients outside of metropolitan centres presents a dilemma of inequity, with limited workflow data hindering benchmarking and service optimisation. Aims To analyse key stroke treatment time parameters from a primary stroke centre existing in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Together with the medical history and clinical examination we should distinguish between stroke mimics and AIS. The process described here with very short DIDOs is in accordance with the strong recommendations of earlier studies when aiming at better outcomes for AIS patients with LVOs [17][18][19].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Together with the medical history and clinical examination we should distinguish between stroke mimics and AIS. The process described here with very short DIDOs is in accordance with the strong recommendations of earlier studies when aiming at better outcomes for AIS patients with LVOs [17][18][19].…”
Section: Discussionsupporting
confidence: 72%
“…In patients with emergent LVO, long DIDO time seems to have a deleterious effect on outcome and may be the most important modifiable factor in onset to recanalization time in a PSC [14,23]. Although longer median times have been reported [17,19,24], it has recently been shown that it is possible to achieve a median DIDO time of 60 minutes [19]. In this case report on three AIS patients with very short time intervals, we did not study the median DIDO time, which may constitute a weakness.…”
Section: Discussionmentioning
confidence: 99%
“…In the overall cohort, median (IQR) DIDO time was 66 (52-83) min (Table 1). In 125 patients with available imaging times, median (IQR) DIDO time was 66 (53-84), door-tonon-contrast enhanced CT-scan (NCCT) time was 16 (12)(13)(14)(15)(16)(17)(18)(19)(20) min, NCCT-to-CTA time was 9 (6-11) min, CTA-to-ambulance notification time was 24 (16-37) min and notification-to-departure time was 15 (10-21) min. Mean (±SD) CTA-to-ambulance notification time was the longest component of mean DIDO time with 29 (±20) min (38.7%) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…17 Another cohort study conducted in Australia, did not identify statistically significant determinants for DIDO time in 55 patients with a median DIDO time of 120.5 min. 18 Finally, a more recent cohort study conducted in the United States found a median DIDO time of 148.5 min in 191 patients, where CTA acquisition at PSC, walk-in arrival mode, administration of IVT, intubation at PSC and ambulance request by PSC were independently associated with DIDO time. 19 Generally, the median DIDO times in these studies were long and study populations small.…”
Section: Discussionmentioning
confidence: 97%
“…Metrics such as DIDO are an ideal target for quality improvement and have been shown to correlate with stroke outcomes 3. These time metrics are important as they serve as objective measures of the overall performance of a complicated process currently involving multiple organisations 6 7. In Victoria, air transport of patients may be organised by either Ambulance Victoria or Adult Retrieval Victoria depending on the clinical status of the patient.…”
Section: Discussionmentioning
confidence: 99%